The Influence Of Tone At The Top, Locus Of Control, And Tone At The Bottom On Dysfunctional Audit Behavior - Khoirotun Nikmah; Zul Azmi (Riau International Conference on Economics, Business and Accounting, 2025)
The purpose of this study is to investigate the influence of locus of control, tone at the top, and tone at the bottom on dysfunctional audit behavior. It examines both internal and external factors that may lead auditors to commit fraud or deviate from established audit standards. The research involved distributing questionnaires to all auditors at the Pekanbaru Public Accounting Firm, totaling 60 participants. A quantitative approach was employed, utilizing a saturated sampling method to determine the sample size. Tone at the top was assessed through performance pressure and company regulations; locus of control was evaluated based on external and internal dimensions; and tone at the bottom was gauged by expectations of non-compliant behavior from coworkers and actual instances of non-compliance among colleagues. The findings indicated that tone at the top, locus of control, and tone at the bottom all had a positive and significant impact on dysfunctional audit behavior.